Whole-body PET/MRI to detect bone metastases: comparison of the diagnostic performance of the sequences - Ulusoy Onur Levent; Server Sadık; Yesilova Murat; İnan Nagihan (Radiology and Oncology)
Whole-body positron emission tomography/magnetic resonance imaging (WB-PET/MRI) is increasingly used in the initial evaluation of oncology patients. The purpose of this study was to compare the diagnostic performance of WB MRI sequences, attenuation-corrected raw data positron-emission tomography (AC PET), and PET/MRI fused images to detect bone metastases.